A comparative study of the dissolution profiles of two commercially available theophylline preparations - Laddaran, Christopher S.; Romano, Marites B.; Bautista, Jocelyn S. (Manila College of Pharmacy, University of the Philippines, 1996)
In vitro dissolution profiles of commercially available theophylline preparations (one tablet and one capsule) were made using USP Apparatus 2 (paddle assembly) at a period of 9 hours. The dissolution profile of an immediate release preparation (tablet) was also obtained. A UV spectrophotometer at a wavelength of 270 nm was used to evaluate drug release at every time interval. Their percentage release and percent labelled claim were also obtained.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, MArch 1996.
Keywords: Theophylline